Depressive symptoms among healthcare undergraduate students - Julia Zancan Bresolin; Graziele de Lima Dalmolin; Silvio José Lemos Vasconcellos; Edison Luiz Devos Barlem; Rafaela Andolhe; Tania Solange Bosi de Souza Magnago (Universidade de São Paulo, 2020)
Objective: to identify the intensity of depressive symptoms and their associated factors in healthcare undergraduate students. Method: cross-sectional study developed with undergraduate health students from a public higher education institution using the Beck Depression Inventory-version II and a student characterization questionnaire. The study involved 792 participants. For data analysis, we used descriptive statistics, chi-squared test and Poisson regression. Results: the intensity of depressive symptoms was moderate to severe in 23.6% of the students, associated with the non-performance of physical and leisure activities and with speech therapy and nursing courses. Conclusion: several factors may be associated with depression, thus, further investigation into the related factors that cause its emergence in this period of life is necessary, as well as raising institutional awareness and developing strategies at the personal and group level to promote well-being, improve time management and interpersonal relationships, in order to achieve better academic results and personal development.